Growth and pathogenesis of Enteropathogenic E.coli as affected by bacteriocin produced and purified from Lactobacillus isolates with or without Quercus infectoria: Hassan A. Abdul-Ratha¹ , Essam F. Al-Jumaily² and Rana H. Raheema - Abdul-Ratha, Hassan A. (The Iraqi Journal of Veterinary Medicine, 2012)
The antimicrobial activity of Lactobacilli has been widely exploited for prevention offood –borne pathogens e.g.: Escherichia coli being the major cause of diarrhea especially inchildren, because of bacteriocin activity and the importance of herbal drugs, hence this studywas designed to evaluate the synergistic effect of plant extract and bacteriocin produced byLactobacillus on the growth and pathogenesis of Enteropathogenic Ecoli.1. The Plantaricin production was induced by adding the mutagenic agent Mitomycin C.2. Purification of Plantaricin was made by heating crude plantaricin at 80ºC for 10min andthen purified by two steps method including extraction with n-butanol followed by gelfiltration chromatography on Sepharose 6B column. The results showed that the specificactivity was 1600 AU/mg protein with 8 purification folds and 12% recovery yield.3. The antibacterial activity of Quercus infectoria with concentration 300 mg/ml wasshowed highly antibacterial activity in vitro and in vivo.4. The result showed synergistic effect of Plantaricin with Quercus infectoria extract afterexperimental infection that induced by orally dosing with Escherichia coli in vivo. A result ofhistopathological study was recorded recovery of tissue.